Primary Splenic Leiomyosarcoma With Metastasis in a Rhesus Monkey (Macaca mulatta) - Matthew F. Starost (Veterinary Medicine and Science)
ABSTRACT Primary mesenchymal tumours of the spleen in non‐human primates are exceedingly rare. We report on a 13‐year‐old female rhesus monkey who had an enlarged liver, spleen and multiple lung masses. Macroscopic, microscopic and immunohistochemical examinations revealed a splenic leiomyosarcoma with widespread metastasis. This is the first report of a splenic leiomyosarcoma in a non‐human primate.